FEATURE DETECTION BASED ON CORRELATION DETECTION IN COGNITIVE RADIO NETWORK - Sura Khalid Tawfeeq; Emad A. Mohammed; Razan Abdulhamed (Journal Park Publishing, 2024)
Cognitive radio is a promising technology that proposes to address radio spectrum scarcity by opportunistically distributing idle licensed users to unlicensed ones [1] , As wireless communications increase, more spectrum resources are required. Under the current spectrum structure, the bulk of the spectrum band is only allotted to specific permitted services. However, the underutilization of many permitted bands, particularly those for TV transmission, results in spectrum waste [2]. This has prompted the Federal Communications Commission (FCC) to deploy CR technology to make licensed bands available to unlicensed users [3